Relationship between nutritional status and length of hospital stay among patients with atrial fibrillation – a result of the nutritional status heart study - Czapla, Michał; Uchmanowicz, Izabella; Juárez-Vela, Raúl; Durante, Angela; Kałużna-Oleksy, Marta; Łokieć, Katarzyna; Baeza-Trinidad, Ramón; Smereka, Jacek (Frontiers in Nutrition, 2022)
Background Nutritional status is related to the prognosis and length of hospital stay (LOHS) of patients with atrial fibrillation (AF). This study aimed to assess how nutritional status affects LOHS for patients with AF. Methods We performed retrospective analysis of the medical records of 1,813 patients admitted urgently with a diagnosis of AF to the Institute of Heart Diseases of the University Clinical Hospital in Wroclaw, Poland. Results In total, 1,813 patients were included in the analysis. The average LOHS in the entire group was 3.53 ± 3.41 days. The mean BMI was 28.7 kg/m2 (SD: 5.02). Patients who were hospitalized longer were statistically more likely to have a Nutritional Risk Score (NRS) ≥3 (p = 0.028). A higher percentage of longer hospitalized patients with LDL levels below 70 mg/dl (p < 0.001) and those with HDL ≥40 mg/dl (p < 0.001) were observed. Study participants with NRS ≥3 were an older group (M = 76.3 years), with longer mean LOHS (M = 4.44 days). The predictors of LOHS in the univariate model were age (OR = 1.04), LDL (OR = 0.99), HDL (OR = 0.98), TC (OR = 0.996), CRP (OR = 1, 02, p < 0.001), lymphocytes (OR = 0.97, p = 0.008) and in the multivariate model were age, LDL (mg/dl), HDL (mg/dl), Na, and K. Conclusion For nutritional status, factors indicating the risk of prolonged hospitalization in patients with AF are malnutrition, lower serum LDL, HDL, potassium, and sodium levels identified at the time of admission to the cardiology department. Assessment of nutritional status in patients with AF is important both in the context of evaluating obesity and malnutrition status, as both conditions can alter the prognosis of patients. Further studies are needed to determine the exact impact of the above on the risk of prolonged hospitalization.